Encyclopedia of Polymer and Rubber Additives - Wypych, George; Wypych, George (ChemTec Publishing, 2024)
Encyclopedia of Polymer and Rubber Additives documents how polymer properties and performance can be improved through the use of additives, resulting in enhanced physical properties, stability, improved process and assembly, extended shelf life, enhanced purity, and minimized environmental impact. 88 groups of additives used by all segments of the polymer and rubber industries are included, with each group discussed in a systematic manner in order to facilitate easy information retrieval and comparison. Typical chemical structures, mechanisms of action, influences and interferences in complex formulations, and evidence of performance from experimental studies are each featured, with frequent references to monographic sources for even more in-depth knowledge of the subject. The companion volume, Databook of the Most Important Polymer and Rubber Additives is also available. It contains robust technical data on the most essential additives currently in use, and the two books are must-have references for anyone working with rubbers and plastics. - Provides a complete set of tables, classifications, and information related to a wide variety of commercially used additives for polymers and rubbers - Details the characteristics of hundreds of additives that can improve performance of physical properties, stability, and storage life, provide colorants, reduce costs, enhance purity, and minimize environmental impact - Facilitates information retrieval and comparison, discussing mechanisms of action, suitable features, modifications, evidence of performance from experimental studies, and more